Animal creativity and innovation - Kaufman, Allison B.; Kaufman, James C. (Explorations in creativity research., 2015)
"Animal Creativity and Innovation explores theories and research on animal innovation and creativity, comparing and contrasting it with theory and research on human creativity and innovation. In doing so, it encompasses findings from psychology, biology, neuroscience, engineering, business, ecology, and education. The book includes examples of animal innovation in parrots, dogs, marine mammals, insects, and primates, exploring parallels from creative play in children. The book defines creativity, differentiating it from play, and looks at evolutionary models and neurological constructs. The book further explores applied aspects of animal innovation and creativity including tool use and group dynamics, as well as barriers to creativity. The final chapters look into how creative behavior may be taught or trained. Each chapter is followed by a commentary for integration of thoughts and ideas between animal and human research, behavioral and cognitive research, and theory and observation in real life."--Provided by publisher